A Nonlinear observer-based trajectory tracking method applied to an anaerobic digestion process. (March 2019) - Chaib Draa, K.; Zemouche, A.; Alma, M.; Voos, H.; Darouach, M.
Abstract: In this paper, we present a new systematic method to design observer-based tracking control for a class of linear parameter varying (LPV) systems in the presence of Lipschitz nonlinearities. The work has been motivated by the aim to integrate Biogas Plants (BPs) in the power grid. Hence, due to the lack of autonomous and reliable sensors for anaerobic digestion (AD) processes, an exponential nonlinear observer is incorporated in the control scheme. By using the Young's inequality in a judicious way, new and dilated linear matrix inequality (LMI) conditions are provided to ensure convergence of the tracking error. Due to the complexity of the considered LPV model, an H ∞ -optimality criterion is used to handle the uncertain tracking error dynamics. An extension to discrete-time systems is provided in order to widen the applicability of the proposed method to more general real-world models. Numerical simulations are provided to show the effectiveness of the proposed theoretical methodology.